Mycelium-producing Mushroom Calocybe indica (Milky Mushroom) as Bio-antagonist Against the Bacteria present in Marikina River. - Borela, Vandon; Apolinar, Dhian Ashley; Cuachin, Franz Weslei; Calañada, Laurence James (International Journal Papier Advance and Scientific Review, 2020)
Mushroom forming fungi are one of the nature’s most powerful decomposers and degrades a wide variety of environmentally persistent pollutants and organic contaminants by secreting strong extra cellular enzymes due to their aggressive growth and biomass production. This study assess the potential of Calocybe indica (Milky mushroom) as bio-antagonist against microorganism serves as pollutants on Marikina River through Heterotrophic plate count (HPC). The use of Calocybe indica (Milky mushroom) as the medium of mycoremediation effectively lessen the count of bacterial colonies in Marikina River’s water by creating a bio-antagonistic relationship with the bio-pollutants present on the water samples. Increasing the period of treatment and observation. Using of water samples from different depth from surface level down to aphotic region of the Marikina River. Identifying the strain of microorganisms present on the water. Using other mushroom to compare the potential of Calocybe indica to kill bio-pollutants should be done for the improvement of the study.